Investigating Attitude, Subject Enrollment, and Achievement in Science before Investing in Higher Education: A Comparison of Universities and Non-University Institutions - Bhatti, Dr. Muhammad Tariq; Teevno, Dr. Roshan Ali (The journal of contemporary issues in business and government, 2021)
The field of science is changing the world in many ways ACT (2017); however, studies have reported the students’ lowest achievement and lower enrollment rate in science courses (Fayer, 2017; Filardo, 2016) with a negative attitude towards science (ATS) (Song & Bruning, 2016). Specially, the ATS continues to be the dominant factor; importantly the decline in ATS has emerged recently. Drawing on the ATS in higher education benefits, the current study hypothesized that ATS would possibly a driving force in improving science degree programs in three areas, first, increase in science enrollment, second, promoting higher achievement in science, and finally, raising academic standards through positive attitude of head of departments (HoDs) and vice chancellors (V.Cs). Technically, there is a need for analysis any possible dissonance between students’ ATS and the institution’s (Faculty Members & Head) ATS, as both are necessary for improving enrollment in science, and students’ achievement. This difference of ATS may create a severe problem for students’ performance and/or institutional gross enrollment in science, therefore, we empirically investigated the attitudes of students, parents, the faculty members (FMs), Head of Departments (HoDs), and V.Cs towards science, graduates and postgraduates (G-PGs) academic achievement and enrollment in science. Using stratified sampling technique 1200 G-PGs, 212 faculty members (FMs), 40 HoDs, 500 parents, and 15 Vice Chancellors (VCs) /Vice-Presidents from fifteen universities/non-university institutions (NUIs) selected.. We analyzed the ATS of 1967 participants thorugh stratified sampling technique included from fifteen higher education institutions (universities/NUIs) of Sindh, to identify whether ATS affects students’ achievement, and subject enrollment in both types of institution. A panel of experts and pilot testing refined the data instruments. The overall Cronbach alpha value was 0.87 and 0.89 for Test of Science Related Attitude (TOSRA) Students’ and Subjects Choice Sheet (SSCS) respectively.All participants’ ATS explored through Test of Science Related Attitude (Fraser, B., & Lee, S. 2015), while G-PGs’ grades of midterm and final test results considered as marks in science. Similarly, students’ science course enrollment explored through Students’ Subjects Choice Sheet (SSCS). We administered descriptive statistics, and ANOVA (‘F’- ratio), Correlation Coefficient r, and t- tests. Results identified a positive relationship between ATS [F (2, 1198) = 485.347, p = .05], science achievement [F (2, 1198) =18.907, p = .05]. Furthermore, the personal information pool and the student’s self-ATS, are mainly responsible for the student’s subject enrollment in science. We presented reasonable and practically applicable recommendations.